LINC01270 Regulates the NF-κB-Mediated Pro-Inflammatory Response via the miR-326/LDOC1 Axis in THP-1 Cells - Imene Arab; Su-Geun Lim; Kyoungho Suk; Won-Ha Lee (Cells, 2024)
Long intergenic noncoding (LINC)01270 is a 2278 bp transcript belonging to the intergenic subset of long noncoding (lnc)RNAs. Despite increased reports of LINC01270’s involvement in different diseases, evident research on its effects on inflammation is yet to be achieved. In the present study, we investigated the potential role of LINC01270 in modulating the inflammatory response in the human monocytic leukemia cell line THP-1. Lipopolysaccharide treatment upregulated LINC01270 expression, and siRNA-mediated suppression of LINC01270 enhanced NF-κB activity and the subsequent production of cytokines IL-6, IL-8, and MCP-1. Interestingly, the knockdown of LINC01270 downregulated expression of leucine zipper downregulated in cancer 1 (LDOC1), a novel NF-κB suppressor. An analysis of the LINC01270/micro-RNA (miRNA)/protein interactome profile identified miR-326 as a possible mediator. Synthetic RNA agents that perturb the interaction among LINC01270, miR-326, and LDOC1 mRNA mitigated the changes caused by LINC01270 knockdown in THP-1 cells. Additionally, a luciferase reporter assay in HEK293 cells further confirmed that LINC01270 knockdown enhances NF-κB activation, while its overexpression has the opposite effect. This study provides insight into LINC01270’s role in modulating inflammatory responses to lipopolysaccharide stimulation in THP-1 cells via the miR-326/LDOC1 axis, which negatively regulates NF-κB activation.